2013
DOI: 10.1039/c3dt51691a
|View full text |Cite
|
Sign up to set email alerts
|

6-Substituted purines containing thienyl or furyl substituents as artificial nucleobases for metal-mediated base pairing

Abstract: The artificial nucleobases 6-(2'-thienyl)-purine (6TP) and 6-(2'-furyl)-purine (6FP) have been investigated in terms of their applicability in metal-mediated base pairs. In principle, these nucleobases should be capable of providing an S,N- and O,N-coordination environment, respectively. Two metal complexes have been synthesized and structurally characterized, using the N9-methylated derivatives of 6TP and 6FP as model nucleobases. The silver(I) complex [Ag(9-Me6TP)(CH3CN)(NO3)]n is of polymeric nature. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 54 publications
0
37
0
4
Order By: Relevance
“…An analogous 26mer sequence has previously been investigated with other artificial metal-mediated base pairs [25,30], allowing a direct comparison of the results. Similarly, various [14,[26][27][28][29]35].…”
Section: Investigation Of the Metal-binding Properties Of The Dna Dupmentioning
confidence: 97%
“…An analogous 26mer sequence has previously been investigated with other artificial metal-mediated base pairs [25,30], allowing a direct comparison of the results. Similarly, various [14,[26][27][28][29]35].…”
Section: Investigation Of the Metal-binding Properties Of The Dna Dupmentioning
confidence: 97%
“…1) The melting temperature T m of duplex I in the absence of any transition metal ion (38.9°C) is amongst the highest observed for all previously investigated duplexes. For comparison, T m was ranging from 21.6 to 30.4°C for base pairs involving bidentate "click" nucleosides [29,30] and from 39.1 to 42.9°C for 6-substituted purines [35]. Merely the duplex comprising a 6TP:6TP mispair (6TP = 6-thienylpurine) has a significantly higher melting temperature (42.9°C) [35].…”
Section: Hetero Base Pair Comprising the Tridentate Ligand And Imidazolementioning
confidence: 99%
“…2. This particular sequence was chosen because several other metalmediated base pairs have previously been investigated in this sequence context [29,30,34,35], enabling a detailed comparison of their respective properties. Two related duplexes were investigated, i.e.…”
Section: Synthesis Of the Dna Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…28,42 The artificial nucleobase 6-furylpurine (6FP) (Figure 4c) investigated in this context is of particular interest, as it in principle allows the formation of an Ag(I)-mediated base pair both via its WatsonCrick edge and via its Hoogsteen edge. 28,49 A comparison of both base pairing patterns indicated that the one adopted in parallel-stranded DNA is significantly more stabilizing than that in antiparallel-stranded DNA. Such large increases in T m are an important prerequisite for the use of a metalmediated base pair in a sensor application.…”
Section: Pymentioning
confidence: 99%